Sonodynamic biomimetic-nanomedicine fight cancers - Anni Zhang; Xu Zheng; Guangqi Yan; Xiaoqi Liu; DongXuan Xie; Xiaohe Xu; Mengchi Sun; Zhijun Liu (Journal of Nanobiotechnology)
Abstract Sonodynamic therapy (SDT) represents an innovative oncological treatment modality that harnesses the synergistic effects of low-intensity ultrasound and sonosensitizers to kill tumor cells. However, this dynamic therapeutic strategy faces multiple obstacles, including physicochemical barriers in the tumor microenvironment (TME) and the potential toxicity of off-target sonosensitizers, which may accumulate in off-target sites and be non-specifically activated by ultrasound, leading to damage of normal tissues. Recently, biomimetic-nanomedicine platforms, specifically designed to target the TME challenges, have emerged as a potent solution, enabling the development of SDT that enhance therapeutic outcomes, which even derives the concept of the sonodynamic biomimetic-nanomedicine (SBNM). In light of the states, we herein aim to summarize a cutting-edge review on the rapid advances of SBNM. Firstly, tumor-killing mechanisms and development and classification of sonosensitizers are outlined. In addition, recent progresses in various biomimetic-nanomedicines, containing red blood cell membrane-coated, immune cell membrane-coated, cancer cell membrane-coated, hybrid membrane-coated, exosomal and microbial mimicking, are described in the development of preclinical research. Importantly, we offer an in-depth presentation for the superiority of SBNM designed to address physicochemical barriers of TME and abnormalization of the anti-tumor immunity. Last but not least, the challenges and perspectives related to SBNM are also discussed. Graphic Abstract